Can people value the aesthetic and use services of urban sites? Evidence from a survey of Belfast residents - Anna Alberini; Patrizia Riganti; Alberto Longo (Fondazione Eni Enrico Mattei (FEEM), 2002)
This study explores the potential of conjoint choice analysis for planning decisions in urban sites. We elicit people's preferences for regeneration projects that change the aesthetic and use character of specified urban sites. We focus on two sets of regeneration projects. The first set entails hypothetical transformations of an actual square with an important cultural and historical dimension. The other set of projects consists of hypothetical transformations of an abstract square. Each regeneration project is defined by aesthetic and use attributes. Our results suggest that people behaved in a way that is consistent with the Random Utility Model for the abstract square, and that there are both similarities and differences between preferences for the actual and the abstract square.
Keywords: Q26; R14; Z10; 330; conjoint analysis; conditional logit; consumer behavior; aesthetic and use values; urban regeneration; Stadtsanierung; Willingness to pay; Belfast